Taxonomy of the sea stars (Echinodermata: Asteroidea) from Bahia State, including ontogenetic variation and an illustrated key to the Brazilian species - Cunha, Rosana; Martins, Luciana; Menegola, Carla; Souto, Camilla (Zootaxa, 2021)
Describing ontogenetic morphological change is an important part of integrative taxonomy; still, most taxonomic studies are based only on adult characters. Here, we provide illustrations and a morphological description of the sea stars from Bahia, including ontogenetic and intraspecific variation, and identify taxonomic issues. A total of 293 specimens from different localities along the Bahia State coastline and comparative material from other localities were examined. Eighteen species (11 genera, eight families) of Asteroidea were identified; Astropectinidae was the most representative family. All species identified also occur in subtropical Brazilian waters and most species are from shallow water habitats with soft bottoms. Most observed ontogenetic variation was quantitative in nature, such as the increase in the number of spines in the furrow and of spinelets in the paxillae with specimen growth. Genera that require further taxonomic studies are Astropecten and Othilia, whose specimens are commonly misidentified in local studies. One third of the species from Bahia are currently classified as “Vulnerable” in the Brazilian Red List, but baseline data on the population biology of these species are scarce. An illustrated identification key to the 65 Brazilian sea star species is also provided. This taxonomic study will facilitate the identification of specimens occurring along the Brazilian coast and help scientists and policy makers to establish the conservation status of the Brazilian species.